If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + 38x + -2 = 0 Reorder the terms: -2 + -9x + 38x = 0 Combine like terms: -9x + 38x = 29x -2 + 29x = 0 Solving -2 + 29x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 29x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 29x = 0 + 2 29x = 0 + 2 Combine like terms: 0 + 2 = 2 29x = 2 Divide each side by '29'. x = 0.06896551724 Simplifying x = 0.06896551724
| 4.5+6*0.1= | | log(46-4x)=1 | | x^2+20x+26=0 | | y=0.5x+-2 | | 11x+55=254 | | 7-(7-7)/7•9 | | s(t)=64t-16t*t | | 5n^2+19n-68=-28 | | (2)(3)*(1)(3)= | | log(20x)=3 | | 2x^4-20x^2=-18 | | -8-x=4x-33 | | 25-6k=-5k | | 6/8-3/4=0 | | F(5)=9 | | 7x-9=-x+63 | | 2x^2+5x-38=0 | | 18.1-x=-0.165*x | | -g^2-r^2-2rg+49=0 | | 5(x-7)=3(2x-4) | | G(-3)=7 | | 51+x=3(9+x) | | -9+4x=7x+6 | | 90=b+15b+30+15+2b-9 | | -(K+2)x^2-2Kx^2= | | 8=6+h | | 6t-4=3(2t-5)+t | | (51+x)-9=x | | 685-85/12 | | Y-26=-19 | | -9x+38=2 | | (51+x)-(9+x)=x |